Devouring the father: family and recuperation in Triomf and the Native Commissioner - Emmett, Christine (Department of English Language and Literature, 2015)
This thesis seeks to account for the largely unprecedented vigour of white writing in post- apartheid South Africa. Though there are a number of contributing socio-economic factors, it argues that there is an inherent ambivalence in many texts written by white South African authors. Texts that are generally designated as 'reconciliatory' or 'reconstitutive' have a latent imperative. The ambivalence of these texts is exposed by my analysis of two prominent South African novels, Marlene Van Niekerk's Triomf and Shaun Johnson's The Native Commissioner. Alongside this concern, is the fact that the white South African family, regulated and constructed by apartheid legislation, provides one means through which post-apartheid white identity can be anatomized. Therefore, the methodology of this thesis is acritical application of Freud's Oedipal family structure and its attendant primal scene. Through this application we find that Van Niekerk's novel is preoccupied with subverting patriarchal Oedipal structures. This is expressed by the dysfunction of the Benade family. One aspect of this subversion is the dissipating and illegitimate patriarch, and his unremarkable death Mol, the mother, is analysed in terms of her disruptive and chaotic power, as well as her dispensation of narrative. The problem with Van Niekerk's text is that itis incapable of suggesting a post-apartheid Afrikaner (white) identity. This is indicated both by slippages in her portrayal of Mol, and by her attempt to counter-position lesbianism as a viable post-apartheid identity. Therefore, the text exposes an anxiety about paternal authority, suggested by the patriarch's death on voting day. Ten years later, I argue, Shaun Johnson attempts to recuperate this paternal white power in his text, The Native Commissioner. In Johnson's novel, George Jameson is represented as a benevolent bureaucrat and a loving father. I argue that though Johnson attempts to represent George's profession as encroaching upon the benign space of family. This is a false opposition in that colonial paternalism is implicit in George's identity as a father. By focussing on the recurrent image of the garden, I proceed to indicate that this novel is primarily about negotiating the Oedipus complex. By reliving the conflict through narration, the narrator identifies with the dead father. In the Oedipus complex, identification results in remorse and guilt, enacting a transmission of power from father to sons. I argue that this text is latently invested in this transmission of power. This indicates that at the heart of the text is an imperative to recuperate the lost paternalistic white power which the narrator's father represents. Therefore, through these analyses I show that the ten year trajectory represented by Triomf and The Native Commissioner latently enacts a process of loss and recuperation which concerns itself with white illegitimated power. This positions mothers in the novels as representing the illegitimacy of this power, and has the capacity to reflect on the ambivalence inherent in post-apartheid white narratives.